Tadeusz Czeżowski – obszary filozofowania - Słomski, Wojciech (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Artykuł przedstawia poglądy Tadeusza Czeżowskiego, który był jednym z najwybitniejszych przedstawicieli szkoły lwowsko-warszawskiej. Sformułował szereg reguł określających sposób postępowania w nauce. Najważniejszym wnioskiem jest stwierdzenie, że także teorie metafizyczne mają określoną strukturę logiczną, czyli są interpretacjami logiki, nic zatem nie stoi na przeszkodzie, by również metafizykę uznać za dziedzinę nauki. Według Czeżowskiego istnieją dwa rodzaje teorii etycznych: etyka empiryczna oraz etyka dedukcyjna. Czeżowski jednak nie podjął próby stworzenia własnego systemu etycznego.

This article presents the views of Tadeusz Czeżowski, who was one of the most prominent representatives of the Lviv-Warsaw school. He formulated a number of rules defining the rules of conducting science. His most important conclusion is that also metaphysical theories have a specific logical structure, i.e. they are interpretations of logic, therefore there is nothing to prevent metaphysics from also being considered as a branch of science. According to Czeżowski, there are two types of ethical theories: empirical ethics, and deductive ethics. Czeżowski, however, did not attempt to create his own ethical system.
Keywords: Tadeusz Czeżowski; filozofia; nauka; historia filozofii; filozofia polska; Czeżowski; philosophy; science; history of philosophy; Polish philosophy